Pengaruh jenis bahan dan jumlah gigi perontok terhadap kinerja mesin thresher sebagai perontok padi - Setiawan, Agus; Dharma, Untung Surya; Budiyanto, Eko (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2020)
In this technological world, mechanical engineering is inseparable from the existence of a tool and machine that plays an important role in everyday life such as agricultural machinery. This study aims to determine the effect of the type of thresher material, variations in the number of thresher teeth, grain quality, maximum capacity. The method used in this research is literature study, direct observation or observation. Based on the results of measurements and testing with three variations of 3 different thresher teeth materials, the required data is obtained and the data is processed and calculated that the material of bolts, iron bolt, and per leaf, is increasing from 3 different variations in the level of thresher teeth crookedness the bolt material reaches 60o and in the molten iron thresher the bending level rises to 63o whereas in the iron threshold of iron teeth per leaf the smallest is 32o. After conducting direct field testing we can find out that the quality of rice in the variation of the number of thresher teeth 36 thresher teeth reached 40.2 kg, the variation of 40 reached 43.7 kg, and the variation of 44 thresher teeth reached 44.5 kg. Variation 44 teeth thresher has the highest results.